STRATEGI KETUA ORGANISASI SISWA INTRA MADRASAH (OSIM) MENJALANKAN RODA ORGANISASI PADA MAN INSAN CENDEKIA TAPANULI SELATAN TAHUN 2023 - Balyan Oslerking Siregar (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2024)
This research was conducted to find out the history of the founding of OSIM for the first time at MAN Insan Scholar South Tapanuli and the strategy of the chairman of OSIM for the 2022/2023 period of MAN Insan Scholar South Tapanuli using qualitative research methods and to find out OSIM's work program as set out in the organization's vision and mission. What steps are taken in carrying out the activities to be carried out or how does he deal with the challenges he faces when he finds problems in the organization he leads so that the activities that have been formulated run well? This aims to develop students' interests and talents which are developed through a forum at a madrasa or school. The forum in question is an institution or organization for the students themselves. Apart from being a forum for developing students' interests and talents, OSIS or OSIM can also be a means for students to train their leadership, namely becoming chairman of the OSIS or OSIM. The strategy and communication carried out by the OSIM chairman to madrasa leaders and stakeholders as well as coordination with OSIM management elements under his leadership are the keys to success in running the organization well.